FERRIC-FERROUS RATIO AND OXYGEN FUGACITY CALCULATIONS FOR PRIMITIVE MANTLE-DERIVED MELTS: CALIBRATION OF AN EMPIRICAL TECHNIQUE - Danyushevsky L.V.; Sobolev A.V. (My University, 1996)
Several experimentally-based, empirical calibrations of the fO2 of natural silicate melts at atmospheric pressure as a function of melt composition, melt Fe2+/Fe3+, and crystallization temperature have been developed (e.g.Sack et al., 1980;Kilinc et al., 1983;Kress andCarmichael, 1988;Borisov andShapkin, 1990). Cr-Al spinel is a liquidus phase of primitive mantle-derived melts, and is commonly found as inclusions in near-liquidus phenocrysts (mainly olivine). The established atmospheric pressure correlation between Fe2+/Fe3+ values in spinel and coexisting melts over a broad range of basaltic compositions (Maurel andMaurel, 1982) can be used to calculate the Fe2+/Fe3+ value of a melt if the composition of the equilibrium spinel is known. Compositions and crystallization temperatures of primitive melts can be determined by experimental studies of melt inclusions trapped by early-formed refractory phenocrysts. Thus, the association of spinel and melt inclusions in early liquidus phenocrysts can be used to estimate fO2 conditions at the time of their crystallization. In this paper, we present a calibration of this method and discuss its applications. We conclude that combination of the equations ofMaurel andMaurel (1982) andBorisov andShapkin (1990) can be used to calculate fO2 with an accuracy of ±0.71og units, when liquidus spinels have TiO2 <2.5 wt% and Cr2O3 > 13 wt.%, and melt compositions are in the range from basaltic to picritic with H2O contents <6 wt.%. Using this technique we find ΔNNO fO2 values of −0.8 to −1.4 for MORB dredged at the VEMA Fracture Zone in the Atlantic, and 0 to + 1 for Tongan high-Ca boninites.